As religiões de matriz africana e a intolerância religiosa: um retrato do racismo estrutural nos municípios de Recife, Olinda e Jaboatão 2010 - 2019. - Farias, Lucy Patrícia da Silva de (2021)
Brazil, in the Federal Constitution of the Republic, makes reference to the secularity of the State, guaranteeing everyone freedom of belief and the free exercise of such prerogatives. It also determines that no one will be deprived of rights due to religious belief or philosophical or political conviction. This is a characteristic feature of the Democratic State of Law, which has in the legal system means for individuals to act when violated constitutional or legal determinations. However, even with this support, discrimination and prejudice against Africanbased religions are still present in the social context, thus demonstrating that living in public spaces is a daily struggle for respect and against intolerance. Intolerance is an attitude that is based on prejudice, discrimination, pre-judgment, having a social, ideological, philosophical, historically constructed, pervading power relations. Often it is presented in a veiled way, remaining on the plane of subjectivity and, when explicit, several actions are triggered so that the crime is typified. However, the position of the black movement aims for religious intolerance to be framed as religious racism, according to Law 7.716 / 89. In view of this, the present essay presents several aspects that permeate intolerance and, therefore, methodologically, it is an approach that is both quantitative and qualitative. Regarding the quantitative aspect, using as a data collection instrument the information provided by the Ministry of Women, Family and Human Rights (MMFDH) counted through dial 100 and also the data provided through the Infopol/GACE/SDS System. And, the qualitative aspect being based on documentary, bibliographic and field research, with interviews with the people of the terreiro, as well as representatives of the Public Ministry, highlighting the municipalities of Recife, Olinda and Jaboatão dos Guararapes. The analysis of the interviews is based on the argumentation of the discourse following the French line based mainly on Pêcheux and Orlandi. And, depending on the data, crimes are usually classified as religious feeling, qualified injury or racism. However, the main reasons evidenced were: structural racism, the difficulty of coexistence in public spaces, new mechanisms of criminalization, power relations and the persecution of neo-Pentecostals.